INCOME ANALYSIS AND SATISFACTION LEVEL OF OIL PALM SMALLHOLDERS WITH THE SMALLHOLDER OIL PALM REPLANTING PROGRAM IN OKU DISTRICT - Ardi, Ardi; Fifian, Fifian Permata Sari; Yetty Oktarina (International Journal of Social Science, 2024)
Oil palm (Elaeis guinensis jack) is one type of plantation crop that occupies the most important position in the agricultural sector, this research was conducted in Markisa Village, Lubuk Batang District, OKU Regency. Determination of the location was carried out intentionally (Purposive), the research method used in this research is the case study method considering that in Markisa Village the only area in OKU Regency that has implemented the PSR program from the government, the sampling method used in this research is purposive sampling method. Data analysis processed in the research is primary and secondary data. Primary data was used to analyze income and satisfaction level. Secondary data is used to see the data from KUD Perkasa Jaya, while to answer the first problem of the study used income analysis and to answer the second problem formulation in using IPA analysis (Importance Performance Analysis). Based on the results of the study, the average income of oil palm farmers after participating in the PSR Program with KUD Perkasa Jaya is Rp 67,549,610 / year / farmer or Rp 19,248,007 / ha / year. Based on the analysis of the level of satisfaction using the IPA method, it is concluded that the attributes of administrative services and technical services that have met the level of satisfaction of oil palm farmers. While the attributes that have not met the level of satisfaction of farmers are attributes Production facilities. Based on the results of the level of satisfaction between the level of importance and the level of performance has a score of 4.8 the lowest is included in the interval value with the category of performance attributes production facilities are not high. That is, it has not been able to meet the level of satisfaction of oil palm farmers